Comparative evaluation of hard and soft tissue parameters by using short implants and standard long implants with sinus lift for prosthetic rehabilitation of posterior maxilla - Farhan Durrani; S. M. Karthickraj; Fouzia Imran; Shweta Ahlawat; Ekta Kumari; S. U. Gokila Vani (Wolters Kluwer Medknow Publications, 2024)
Objective: The objective is to compare and evaluate the hard and soft tissue parameters by using short and standard long implants with sinus lifting in the posterior maxilla. Materials and Methods: Eleven patients with complaints of missing upper back teeth were enrolled in the study for implant-supported rehabilitation and were categorized into two groups: Group long (GL): longer implant (>8 mm) placement, preceded by Sinus Augmentation. Group short (GS): short implant (≤8 mm) placement, without sinus augmentation. The primary outcome measured was cumulative survival rate (CSR) in the compromised partial edentulous posterior maxilla. Secondary outcomes measured were implant stability (IS), marginal bone level alterations (MBL), pocket probing depth (PPD), crown-to-implant ratio, and any complications. Results: The difference in CSR between the groups was not statistically significant (P = 0.317). High stability was achieved immediately after the placement of the implants, in both groups (GS: 64 ± 4.07, GL: 65.58 ± 9.75); this difference in the mean ISQ (IS quotients) values was not found to be statistically significant at implant placement (P = 0.7). The mean MBL reported in the study at the end of 12 months of prosthesis function was − 0.762 ± 0.48 mm and − 0.7 ± 0.34 mm for GS and GL, respectively. The mean PPD measurements in GS and GL groups were 1.917 ± 0.68 mm and 1.833 ± 0.38 mm, respectively, and it was not statistically significant (P = 0.8). Conclusion: Within the limitations of the present study, the obtained results indicate that short implants provided a similar clinical and radiographic performance compared to long implants placed in combination with a sinus augmentation procedure (lateral window) up to 12 months after prosthetic loading.